Trade Policy and WTO Accession for Economic Development : Application to Russia and the CIS, Module 1. Trade Policy Principles - Navaretti, Giorgio Barba; Epifani, Paolo (World Bank, Washington, DC, 2017)
This module illustrates the basics of trade policy analysis. It focuses on the following questions: 1) What do countries gain by trading with each other instead of opting for self sufficiency?; 2) What are the main instruments of trade policy?; 3) How do they affect prices, output and welfare?; and 4) What are the effects of trade policy in the presence of market imperfections. This book is arranged as follows: In Section one, the authors show how the main welfare effects of trade policy can be analyzed. In Section two, the authors illustrate the main sources of gains from trade, namely, how and why international trade raises welfare. In Section three, the authors examine the main trade policy instruments and discuss their welfare effects, while in Section four the authors ask whether there is scope for trade policy in the presence of externalities generated by domestic production or when markets are imperfectly competitive. The main issues will be illustrated in very simple and intuitive terms. Boxes will instead provide a more rigorous analysis of the arguments discussed in this module.